The Anti-Arthritic Potential of the Ethanolic Extract of Salvia Lachnostachys Benth. Leaves and Icetexane Dinor-Diterpenoid Fruticuline B - Natália de M. Balsalobre; Elisangela dos Santos-Procopio; Cristhian S. Oliveira; Silvia C. Neves; Maria H. Verdan; Saulo E. Silva-Filho; Rodrigo J. Oliveira; Maria É. A. Stefanello; Cândida A. L. Kassuya (MDPI AG, 2024)
The decoction of Salvia lachnostachys Benth. leaves is used in Brazilian folk medicine for anti-spasmodic, antipyretic, and anxiolytic purposes. Some of the biological effects of an S. lachnostachys extract have been shown to be anti-inflammatory, anti-cancer, and antidepressant effects. In addition, this medicinal plant produces several compounds including icetexane diterpenoids, such as fruticuline A and fruticuline B. The aim of the present work was to evaluate the anti-hyperalgesic and anti-inflammatory properties of fruticuline B (FRUT B) and the ethanolic extract obtained from the leaves of S. lachnostachys (EESL) in experimental mouse models. EESL (30, 100, and 300 mg/kg) and FRUT B (1 mg/kg) were evaluated in articular inflammation-induced models in Swiss mice. In articular inflammation induced by Zymosan, EESL (300 mg/kg) and FRUT B (1 mg/kg) significantly reduced mechanical hyperalgesia (83.17% inhibition for EESL and 81.19% for FRUT B); edema (68.75% reduction for EESL and 33.66% for FRUT B); leukocyte migration (81.3% for EESSL and 92.2% for FRUT B), and nitric oxide production (88.3% for EESL and 74.4% for FRUT B). The exposure to fruticuline B significantly inhibited the edema (51.5%), mechanical (88.12%) and cold hyperalgesia (80.8%), and myeloperoxidase (MPO) (63.4%) activity 24 h after CFA injection. In the pleurisy model, FRUT B reduced 89.1% of leukocyte migration and 50.3% in nitric oxide production. Four hours after carrageenan injection, FRUT B (1 mg/kg) diminished 89.11% of mechanical hyperalgesia, 65.8% of paw edema, and 82.12% of the response to cold hyperalgesia. In the MTT test, EESL and fruticuline B caused no cytotoxicity. The present study revealed, for the first time, the anti-arthritic and anti-nociceptive effects of FRUT B, pointing out the therapeutic potential of the species to control inflammation and nociception. Future studies are needed to evaluate other biological properties of fruticuline B and to better understand its mechanism of action.